Process of development of a contemporary curriculum in advanced midwifery - Maree, Carin (Health SA, 2018)
BACKGROUND: We identified the need for a contemporary curriculum to enhance education in advanced midwifery. Midwifery education needs to address the changing health needs, meet the requirements of the educational framework in South Africa and align with international trends. AIM: The aim was to describe the development of a contemporary curriculum for advanced midwifery. SETTING: The curriculum development took place at a South African university. METHOD: We used a situational analysis to create a contemporary curriculum based on the Research Development and Diffusion Model. RESULTS: We described the process followed for the situation analysis towards the development of a contemporary curriculum in advanced midwifery which is aligned with global trends. CONCLUSION: A situation analysis of the existing curriculum, the community and country’s maternal and neonatal needs, educational framework and global trends should be used to develop the intended contemporary curriculum.